IMPLEMENTASI PIECES FRAMEWORK DALAM PERANCANGAN E-DOCUMENT MANAGEMENT SYSTEM WEBSITE PUSAT JAMINAN MUTU - Cosmas Haryawan; Sari Iswanti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
The Quality Assurance Center (PJM) is an important unit in a university because it carries out activities in the context of improving the quality of higher education. STMIK AKAKOM as one of the universities also has a PJM Unit, but until now document management is still done in a simple way, namely storing the data and documents on the computer belonging to PJM. Meanwhile, specifically for monitoring results, document need to be printed to be distributed to related parties. Both of these things make it difficult to access by internal or external parties. Electronic Document Management System (E-DMS) is needed to facilitate good document maintenance and management so that documents will be easily stored, searched, updated or shared with other parties and has a security when accessed. In system development, proper analysis and design are needed in order to identify the problem and the solution. Evaluation of the condition of the existing system and result of the design are evaluated using the PIECES Framework. Based on the final results, it can be seen that the E-DMS design for the PJM STMIK AKAKOM obtained good results for the 6 evaluation components, namely Performance, Information, Economics, Controls and Security, Efficiency and Service.